The human cytomegalovirus-encoded pUS28 antagonizes CD4+ T cell recognition by targeting CIITA - Fabienne Maassen; Vu Thuy Khanh Le-Trilling; Luisa Betke; Thilo Bracht; Corinna Siegmund; Malte Bayer; Benjamin Katschinski; Antonia Belter; Tanja Becker; Denise Mennerich; Sebastian Voigt; Lori Frappier; et al. (eLife)
Human cytomegalovirus (HCMV) is a relevant pathogen, especially for individuals with impaired immunity. Harnessing potent immune antagonists, HCMV circumvents sterile immunity. Given that HCMV prevents the upregulation of human leukocyte antigen (HLA)-DP and HLA-DR, we screened a library of HCMV genes by co-expression with the HLA class II (HLA-II)-inducing transcription coordinator class II transactivator (CIITA). We identified the latency regulator pUS28 as an interaction factor and potent viral antagonist of CIITA-driven expression of CD74, HLA-DR, HLA-DM, HLA-DQ, and HLA-DP. Both wt-pUS28 and a mutant incapable of inducing G protein-coupled signaling (R129A), but not a mutant lacking the C-terminus, drastically reduced the CIITA protein abundance post-transcriptionally. While control CD4 + T cells from HCMV-seropositive individuals vigorously responded to CIITA-expressing cells decorated with HCMV antigens, pUS28 expression was sufficient to inhibit HLA-II induction and immune recognition by HCMV-specific CD4 + T cells. Our data uncover pUS28 to be employed by HCMV to evade HLA-II-mediated recognition by CD4 + T cells.